Refactoring technical support to reduce interrupts of developers. Issue 11 (28th September 2016) - Kelemen, Zádor Dániel; Tódor, Balázs; Hodosi, Sándor; Somfai, Ákos
Abstract: In this paper an analysis of a technical support data with the goal of identifying process improvement actions for reducing interrupts is presented. A technical support chat is established and used to provide internal developer support to other development teams, which use the software code developed by a core team. The paper shows how data analysis of a 6‐month support time helped to identify gaps and action items for improving the technical support process to minimize interrupts from other developer teams. We show that developers are interrupted through the investigated technical support chat multiple times a day and the interruptions come during the peak working hours. We also show that these interruptions can be prevented with the introduction of multiple tools such as a dispatcher service policy, a dispatcher role, and an FAQ page among others. The paper also shows effects (advantages and drawbacks) of the technical support refactor actions taken on the basis of this analysis. Abstract : The analysis presented in this paper shows that developers can be interrupted many times during core developer hours by support requests. The paper shows how data analysis of a 6‐month support time helped to identify gaps and action items for improving the technical support process to minimize interrupts from other developer teams. The paper also shows effects (advantages and drawbacks) of refactor actions taken on the basis of this analysis.